INTERNATIONAL CONVENTIONS AND THE CURTAILMENT OF RAPE IN NIGERIA: A CRITICAL ANALYSIS - DORCAS JOHNSON (International Studies Journal)
Rape has become a menace across the globe. Nations are utilizing both local and international instruments to combat the epidemic. Despite the existence of numerous legal frameworks and agreements designed to address sexual violence, the prevalence of rape remains alarmingly high in many parts of the world. The hazard is much more worrisome in climes such as Africa, with the high incidences of rape that occur on a daily basis. In Nigeria where national instruments for maintaining law and order appear inefficient following the continues surge of crimes and violence across the nation, there have been recent calls for international interventions. Nigeria is signatory to such international conventions for eradicating violence against women with the hope that such efforts will further boost its effort in combating sexual violence in the country. This article delves into the multifaceted landscape of efforts aimed at curbing the scourge of rape on a global scale, with a particular focus on the impact of international conventions. Utilizing the Declaration on the Elimination of Violence Against Women, this study engaged survey design to interrogate the efficacy of international conventions in combating the endemic scourge of rape in Nigeria. The study engaged survey design with the use of questionnaires and interviews to gather data which Data gathered were analysed and triangulated with secondary data. The study revealed that Nigeria being a signatory to the Declaration on the Elimination of Violence against Women is mainly just on paper with international convention having significant impact in a coordinated coalition against rape in the country. The study therefore recommended the strengthening of existing laws on rape in order to act as some deterrence mechanism to would-be offenders.